Sistem Rekomendasi Produk Sunscreen Berdasarkan Jenis Kulit Menggunakan Metode Forward Chaining Dan Profile Matching - Salma Nuraini; Agung Brastama Putra; Anindo Saka Fitri (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2024)
Skin, as the outermost organ that protects the human body, is susceptible to exposure to external factors such as UV rays, pollution and chemicals, which can have a negative impact and worsen its appearance. Therefore, protecting the skin by using sunscreen is important. The diversity of sunscreen products and skin types sometimes makes it difficult for consumers to choose the right product. To overcome this problem, forward chaining and profile matching methods are applied. Forward chaining is used to determine facial skin type based on existing symptoms to reach conclusions. Next, the Profile Matching method is used to recommend sunscreen products that suit user preferences, by selecting the best alternative based on existing criteria. It is hoped that this research can provide solutions for consumers in choosing the right sunscreen according to their skin type, minimize skin problems that may arise, and increase the comfort of using the product. It is hoped that this research can provide solutions for consumers in choosing the right sunscreen according to their skin type, minimize skin problems that may arise, and increase the comfort of using the product.